CLASSIFICATION OF FACTUAL MATERIAL" AS A SELECTION METHOD - Khaylova, E.G (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
In Russia, children can receive pre-school education from birth. In nurseries, as pre-school educational organizations for the youngest, teachers look after the child, teach him. In the family, a child may not receive upbringing and care, because parents do not know the rules for supervision and early development of children. Counseling centers are being set up so that parents can receive qualified help and support. But the information that parents with young children receive is not always ordered. The task of the research is to develop a method based on the theory and methodology of sociology, philosophy and Philology that allows providing information and suggestions for processing and unifying the system of education and development of children of infant and early ages by educators and parents.